UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN KURIKULUM 2013 - Rusmiati Br Tarigan (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2020)
Abstract This research is motivated by the low ability of teachers in preparing the 2013 Curriculum RPP used in the learning process. Each learning process always includes three main activities namely planning, implementing and evaluating. The learning planning process that must be carried out by the teacher includes the main activities including: making an annual program, making a syllabus, making a semester program, making lesson plans, and making a test / evaluation program. Of the five elements, the lesson plan is the minimum preparation when the teacher will teach in class. To examine the weak performance of teachers in this regard, a study was conducted to determine the effect of the principal's academic supervision on improving teacher competency to develop the 2013 RPP Curriculum. The research method used was a school action research consisting of planning, action, observation and reflection. Data collection techniques using written assignments and observation sheets. The results showed that academic supervision conducted in each cycle through school action research turned out to be able to improve the ability of teachers in preparing the 2013 Curriculum RPP.